Surface modification of PLLA nano-scaffolds with laminin multilayer by LbL assembly for enhancing neurite outgrowth - He, Liumin (2014)
In this study, PLLA nanofibers are fabricated by electrospinning and their surfaces are modified by laminin/chitosan (LN/CS) polyelectrolyte multilayer. Surface C/N ratio determined by XPS analysis quantitatively indicates of discrete coating layers on the nanofibers. The amount of LN deposited sustainably increases with LbL assembly processing, approximately 60 ng mm−2 LN per cycle of LN/CS deposition. The LN-modified PLLA scaffolds significantly induce neurite outgrowth of DRG neurons and NSC compared to the pure PLLA nanofibrous scaffolds. Furthermore, higher amounts of LN adsorbed assist in promoting cell proliferation than PLLA as-spun nanofibers. Therefore, a facile and efficient method to modify nano-scaffolds for the construction of a biomimetic scaffold to promote highly efficient neurite outgrowth is presented.